Mentalization-based treatment versus bona fide treatment for patients with borderline personality disorder in Germany (MAGNET): study protocol of a prospective, multi-centre randomized controlled trial - Sophie Hauschild; Svenja Taubner; Thorsten Vidalón Blachowiak; Ulrike Dinger; Harald Gündel; Sabine C. Herpertz; Jörg Rademacher; Bernhard Strauss; Timo Storck; Ralitsa Vassileva; Ina Burghaus; Manuel Herbst; et al. (BMC Psychiatry)
Abstract Background Borderline Personality Disorder (BPD) is a serious mental disorder. Mentalization-based treatment (MBT) is an evidence-based treatment for individuals with BPD. Specifically, MBT has previously been highlighted for its effectiveness regarding the reduction of suicidal and non-suicidal self-injury (NSSI). Yet, randomized-controlled trials (RCT) on MBT in outpatient settings compared with bona fide treatment (BFT) are still scarce and none has been conducted in Germany. The primary objective of this RCT is to investigate whether outpatient MBT is more effective in the reduction of crisis events (incidences of NSSI and suicide attempts) compared with BFT (namely psychodynamic or cognitive-behavioural psychotherapy) in Germany. Secondary, MBT’s efficacy will be investigated with regard to cost-effectiveness within the German health care system, general and interpersonal functioning, BPD and general symptom severity, social adjustment, quality of life, reduction in psychotropic medication and therapy retention. Additionally, moderator as well as common and treatment specific mediator variables will be investigated. Methods Across 5 study sites in Germany, 304 individuals of all genders from age 18 to 65 with a BPD diagnosis and NSSI or suicide attempts in the past will be asked to participate in the study for a period of two years. In the first year, patients will receive either MBT or BFT and will take part in continuous scientific assessments. Scientific assessments will continue after therapy completion up to a 12-month follow up. As primary outcome, crisis events will be assessed via ecological momentary assessment (EMA) in one week per month (four weekly assessments) during the first year, and in one week every three months during the second year. Number of crisis events up to 2 years post randomization will be compared between treatment arms using a log-linear regression model following an intention-to-treat approach. Secondary outcomes and mediator variables will be assessed at several timepoints. Discussion This study investigates efficacy of MBT as BPD specific treatment in an outpatient setting compared with BFT in Germany. Results of this study can address a treatment gap in the German healthcare system, and inform about health economic aspects of BPD treatment as well as mechanisms of psychotherapeutic change. Trial registration NCT06018272, https://www.clinicaltrials.gov/ , August 30, 2023.